Comparison of kinematics coordination of lower extremity between Elit and professional athletes during roundhouse kick using modified vector coding technique - Heydari, M.; Nazari, A.; Tanbakoosaz, A. (2020 27th National and 5th International Iranian Conference on Biomedical Engineering (ICBME), 2020)
The aim of this study was to compare the kinematic coordination of the lower extremity between elite and professional athletes during Roundhouse kick using a modified vector coding technique. For this purpose, 20 wushu sanda athletes (10 elite and 10 professionals) participated in the study voluntarily. The kinematic data were recorded by lower limb plug in gait biomechanical model and the 12-camera VICON motion capture system. After processing the data, the coordination of the lower limb joints on the sagittal plane was calculated using the vector coding method in MATLAB software. Independent t-test was used for statistical analysis. The findings showed that in ankle and knee coordination, antiphase pattern with more ankle dominancy, in knee and hip coordination, antiphase pattern with knee dominancy, and in hip and pelvic coordination, antiphase pattern with hip dominancy increased in elite athletes. The results of this study showed that the elite athletes, in performing the Roundhouse kick as an open kinematics chain movement, performed the movement transition from the upper joint to the lower joint more optimally. Also, they can support lower joint with a movement reduction in the upper one and perform the movement effectively.